Microstructure evolution and high temperature resistance of Ti6Al4V/Inconel625 gradient coating fabricated by laser melting deposition. (June 2020) - Sun, Zhonggang; Ji, Xiao; Zhang, Wenshu; Chang, Lili; Xie, Guoliang; Chang, Hui; Zhou, Lian
Abstract: High temperature resistant coating is becoming a key technique to improve the heat resistance of aerospace heat-resistant components. In this paper, Ti6Al4V/Inconel625 gradient coating was fabricated by laser melting deposition. The results show that the microstructure changes with composition gradient, from lamellar structure consisting of lamellar α and β phases to equiaxed structure. With the increase of the proportion for nickel-based alloy, alloying elements and concentration of solute increase in molten pool. Furthermore, the nucleation rate increases due to the increase of alloying elements, which leads to the microstructure refinement. The phase composition of gradient coating changes in the sequence of α + β → α + β + Ti2 Ni → Ti2 Ni + β → Ti2 Ni + CrNi2  + γ-Ni. The hardness of gradient coating increases as the relative percentage of Inconel625 correspondingly. When the relative percentage of nickel-based alloy reaches 100%, the hardness reaches a peak of 855 HV1 . The hardness is attributed to the contribution from the formation of Ti2 Ni precipitates, CrNi2 compounds as well as the solid solution hardening. For the high temperature properties, there is a diffusion zone at the interface between Ti6Al4V base layer and transition layer. The transverse microcracks are produced between layers at 800 °C. Graphical abstract: Unlabelled Image Highlights: 90%Ti6Al4V + 10%Inconel625 and 80%Ti6Al4V + 20% Inconel625 were selected as the gradient transition layer. Microstructure changes from lamellar structure to equiaxed structure with the change of composition gradient. Phase changes: α + β → α + β + Ti2 Ni → Ti2 Ni + β → Ti2 Ni + CrNi2  + γ-Ni. It is found that a diffusion zone exists and transverse microcracks are produced when the temperature reaches 800 °C.